The effect of cognitive restructuring counselling technique on reducing students’ social media usage intensity - Irwayanti Irwayanti; Ahmad Yasser (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
The purpose of this research is to discover the effect of cognitive restructuring counseling technique on social media usage intensity of SMPN 1 Bantaeng students. This research uses quantitative approach with Quasi Experimental Design with the Nonequivalent Control Group Design research design. The subjects of this research were 20 students in class VIII who were identified as having high social media usage intensity. The data collection techniques used in this research are usage intensity scaling, observation, and interviews. The results of this research discovers that the implementation of cognitive restructuring technique can reduce the intensity of social media usage intensity as applied according to the procedures that have been designed through 8 meetings. The intensity of using social media before implementing cognitive restructuring technique was considered high but after implementing cognitive restructuring technique, the intensity of using social media decreased.